Presacral Keratinous and Dermoid Cyst Masquerading as Meningocele - A Rare Case Report - Lucky Gupta (Wolters Kluwer Medknow Publications, 2024)
Presacral tumours are rare developmental tumours associated with midline closure defects. A fifteen-month-old girl presented with pain in the lower abdomen and dysuria. After examination, the child underwent investigations and was diagnosed as a presacral mass with intergluteal extension and caudal mass in the subcutaneous tissue of the left gluteal region. Complete excision of mass along with coccygectomy was done. Histopathology showed presacral as a keratinous cyst and gluteal as a dermoid cyst. Later on, the child also developed a left facial dermoid cyst which was also excised.